Trends in public health policies addressing violence against women - Loría, Kattia Rojas; Rosado, Teresa Gutiérrez; Espinosa, Leonor María Cantera; Marrochi, Leda María Marenco; Sánchez, Anna Fernández (Revista de Saúde Pública, 2014)
OBJECTIVE To analyze the content of policies and action plans within the public healthcare system that addresses the issue of violence against women. METHODS A descriptive and comparative study was conducted on the health policies and plans in Catalonia and Costa Rica from 2005 to 2011. It uses a qualitative methodology with documentary analysis. It is classified by topics that describe and interpret the contents. We considered dimensions, such as principles, strategies, concepts concerning violence against women, health trends, and evaluations. RESULTS Thirteen public policy documents were analyzed. In both countries’ contexts, we have provided an overview of violence against women as a problem whose roots are in gender inequality. The strategies of gender policies that address violence against women are cultural exchange and institutional action within the public healthcare system. The actions of the healthcare sector are expanded into specific plans. The priorities and specificity of actions in healthcare plans were the distinguishing features between the two countries. CONCLUSIONS The common features of the healthcare plans in both the counties include violence against women, use of protocols, detection tasks, care and recovery for women, and professional self-care. Catalonia does not consider healthcare actions with aggressors. Costa Rica has a lower specificity in conceptualization and protocol patterns, as well as a lack of updates concerning health standards in Catalonia.